A comparison of contraceptive services for adolescents at school‐based versus community health centers in Oregon. (22nd October 2021) - Boniface, Emily R.; Rodriguez, Maria I.; Heintzman, John; Knipper, Sarah H.; Jacobs, Rebecca; Darney, Blair G.
Abstract: Objective: To compare Oregon school‐based health centers (SBHCs) with community health centers (CHCs) as sources of adolescent contraceptive services. Data sources: Oregon electronic health record data, 2012–2016. Study design: We compared clinic‐level counseling rates and long‐acting reversible contraception (LARC) provision, adolescent populations served, and visit‐level LARC provision time trends. We evaluated adjusted associations between LARC provision and Title X participation by clinic type. Data collection/extraction methods: We used diagnosis and procedure codes to identify contraceptive counseling and provision visits, excluding visits for adolescents not at risk of pregnancy. Principal findings: CHCs were more likely to provide LARC on‐site than SBHCs (67.2% vs. 36.4%, respectively). LARC provision increased more at SBHCs (5.8‐fold) than CHCs (2‐fold) over time. SBHCs provided more counseling visits per clinic (255 vs. 142) and served more young and non‐White adolescents than CHCs. The adjusted probability of LARC provision at Title X SBHCs was higher than non‐Title X SBHCs (4.4% [3.9–4.9] vs. 1.7% [1.4–2.0]), but there was no significant association at CHCs. Conclusions: In Oregon, CHCs and SBHCs are both important sources of adolescent contraceptive services, and Title X plays a crucial role in SBHCs. Compared with CHCs, SBHCs provided more counseling, showed a larger increase in LARC provision over time, and served more younger and non‐White adolescents.